MANAJEMEN PEMBERIAN HUKUMAN (TA’ZIR) DALAM PEMBENTUKAN DISIPLIN SANTRI PONDOK PESANTREN MODERN AN NAJAH CISAUK RUMPIN BOGOR - Alhan, Khusni (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2025)
The aim of this research is to determine he planning of ta'zir in improving discipline and the implementation of ta'zir in improving the discipline of students at the An Najah Cisauk Rumpin Bogor Modern Islamic Boarding School. This type of research is a type of evaluative research with a qualitative approach. This research is field research, the methods used are observation, interviews and documentation. The data source for this research is the management of the An Najah Cisauk Rumpin Bogor Modern Islamic Boarding School. Data analysis used in this research uses data reduction methods which are then presented in descriptive form and verified by drawing conclusions. The results of this research show that planning is good, implementation is effective and the results of the ta'zir program can improve the discipline of students at the An Najah Cisauk Rumpin Bogor Modern Islamic Boarding School